The quest for more research on painful diabetic neuropathy - Nawroth, Peter Paul; Bendszus, Martin; Jende, Johann; Heiland, Sabine; Schmelz, Martin; Schuh-Hofer, Sigrid; Treede, Rolf-Detlef; Kuner, Rohini; Oikonomou, Dimitrios; Gröner, Jan; Kopf, Stefan (Neuroscience, 2018)
This review will use the experts' answers to the questions of the diabetologist, not only to give a summary of the current knowledge, but even more to highlight areas of research needed for improving the fate of patients with painful diabetic neuropathy. Based on the unknowns, which exceed the knowns in diabetic neuropathy, a quest for more public support of research is made.
Available online 20 September 2017
Gesehen am 24.09.2018